Pengaruh Lokasi Tumbuh Terhadap Kadar Flavonoid, Fenolik, Klorofil, Karotenoid Dan Aktivitas Antioksidan Pada Tumbuhan Pecut Kuda (Stachytarpheta Jamaicensis) - Utomo, Daniel Setyo; Elok Kristiani, Elizabeth Betty; Mahardika, Anggara (Bioma : Berkala Ilmiah Biologi, 2020)
Indonesia is a tropical country with high biodiversity of flora and fauna. Jamaica vervain (Stachytarpheta Jamaicensis) is abundance in Indonesia. The purpose of this study is to compare the effect of the habitats to the product of secondary metabolit. Samples were collected from different locations in Central Java: Kopeng (K) (1350 mdpl) and Plamongan Indah, Semarang City (S) (4 mdpl). Fresh leaves are macerated at the room temperature for 48 hours in ethanol solvent. The level of compound were determined by spectrophotometry, while antioxidant activity were analyzed with DPPH method. Data were analyzed using SPSS with the T-test. Levels of flavonoids, phenolic, chlorophyll, and carotenoids (respectively) in the S sample are: 37.11; 8.74; 122.49 and 9.76 mg/L, while the K sample: 20.44; 3.81; 103.74 and 10.23 mg/L. The IC50 value of S sample is 1.17 mg/ml and 2.17 mg/ml in K sample. The results of measurements of environmental conditions in S and soil pH values are 7.0 and 6.8; light intensity of 6300 and 6150 lx, temperatures in the range of 27-38oC and 13-24oC. The growing location affect the levels of flavonoids, phenolics, and antioxidant activity inÂ S. jamaicensisÂ but do not affect levels of chlorophyll and carotenoids.